Host–Parasite Associations in Small Mammal Communities in Semiarid Savanna Ecosystems of East Africa. Issue 4 (25th April 2016) - Guerra, Ana Sofia; Eckerlin, Ralph P.; Dowling, Ashley P. G.; Durden, Lance A.; Robbins, Richard G.; Dittmar, Katharina; Helgen, Kristofer M.; Agwanda, Bernard; Allan, Brian F.; Hedlund, Tyler; Young, Hillary S.
Abstract: Despite the established importance of rodents as reservoirs of vector-borne zoonoses in East Africa, there is relatively limited information regarding the infestation parameters and host associations of ectoparasites that vector many such pathogens among small mammals in this region. Between 2009 and 2013, small mammals were live-trapped in the semiarid savanna of Kenya. A subset of these individual hosts, including 20 distinct host taxa, was examined for ectoparasites, which were identified to species. Species of fleas, ticks, mites, and sucking lice were recorded. Based on these data, we calculated host-specific infestation parameters, documented host preferences among ectoparasites, conducted a rarefaction analysis and extrapolation to determine if ectoparasites were adequately sampled, and assessed nestedness for fleas to understand how pathogens might spread in this system. We found that the flea community structure was significantly nested. Understanding the ectoparasite network structure may have significant human relevance, as at least seven of the ectoparasite species collected are known vectors of pathogens of medical importance in the region, including Yersinia pestis, Rickettsia spp., and Theileria parva, the causative agents of plague, spotted fevers and other rickettsial illnesses in humans, and theileriosis, respectively.